2003
DOI: 10.1249/00149619-200310000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Headache in the Weight-lifting Athlete

Abstract: Weight lifters suffer from the same headache syndromes that affect all human beings. They are also susceptible to headache types brought on by their activity. Three headache syndromes, cervicogenic headache, benign exertional headache, and effort-induced migraine headache, appear to be more common in the weight-lifting athlete. This article discusses the diagnosis and treatment of these headache syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…To the significance of this study, one of the sports which may expose athletes to PEH is resistance training (12). Weight training has been reported as the second most frequent headache-related sports after running (12).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…To the significance of this study, one of the sports which may expose athletes to PEH is resistance training (12). Weight training has been reported as the second most frequent headache-related sports after running (12).…”
Section: Introductionmentioning
confidence: 91%
“…Weight training has been reported as the second most frequent headache-related sports after running (12). The study of Jahani et al on an Iranian population showed that wrestlers had a higher rate of headache prevalence than other athletes (13).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations